Representations of Masculinities in Steven Spielberg”™s Film Text War of the Worlds - Díaz-Cuesta, José (Opción, 2015)
This article follows the four sites Pat Kirkham and Janet Thumin propose in order to study the representation of masculinities in film: the body, action, the external world and the internal world. These sites are applied to Steven Spielberg”™s War of the Worlds. The body of the main male protagonist belongs to a well-known star shown in working-class clothes. One of his most highlighted actions is to be metaphorically reborn. His external world relies on his role as a father, and his internal world asks the question “to what extent can you go to save your family, country or planet?”